2020
DOI: 10.46481/jnsps.2020.139
|View full text |Cite
|
Sign up to set email alerts
|

Alpha decay half-lives of 171-189Hg isotopes using Modified Gamow-like model and temperature dependent proximity potential

Abstract: The alpha decay half-lives for $^{171-189}\mathrm{Hg}$ isotopes have been computed using the Gamow-like model (GLM), modified Gamow-like model (MGLM1), temperature-independent Coulomb and proximity potential model (CPPM), and temperature-dependent Coulomb and proximity potential model (CPPMT). New variable parameter sets were numerically calculated for the $^{171-189}\mathrm{Hg}$ using the modified Gamow-like model (termed MGLM2). The results of the computed standard deviation indicates that the modified Gamow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Our calculated results indicated that for the nuclei having the larger proton number , the experimental data can be better reproduced. Recently, W A Yahya computed the α decay half-lives for 171−189 Hg isotopes using the Gamow-like model, modified Gamow-like model, temperature-independent Coulomb and proximity potential model and temperature-dependent Coulomb and proximity potential model, it is found that the calculated α decay half-lives obtained by using the modified Gamow-like model, temperature-independent Coulomb and proximity potential model are in better agreement with the experimental data [66].…”
Section: Resultsmentioning
confidence: 63%
“…Our calculated results indicated that for the nuclei having the larger proton number , the experimental data can be better reproduced. Recently, W A Yahya computed the α decay half-lives for 171−189 Hg isotopes using the Gamow-like model, modified Gamow-like model, temperature-independent Coulomb and proximity potential model and temperature-dependent Coulomb and proximity potential model, it is found that the calculated α decay half-lives obtained by using the modified Gamow-like model, temperature-independent Coulomb and proximity potential model are in better agreement with the experimental data [66].…”
Section: Resultsmentioning
confidence: 63%
“…The experimental input data used in this study have all been extracted from the NUBASE2020 database [41][42][43]. The orbital angular momentum carried by the emitted α particle was calculated via the spinparity selection rule given by [6,29]:…”
Section: Resultsmentioning
confidence: 99%
“…The Gamow theory explained that the α-decay was as a result of the quantum mechanical tunnelling of a charged α particle through the nuclear Coulomb barrier [4]. Since then, many theoretical models and empirical formulas have been employed in the investigation of α-decay half lives of nuclei [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Some of the successful empirical formulas in the calculations of α-decay half-lives include Viola and Seaborg formula (VSS) [20], Brown formula [21], Royer formula [22,23], Poenaru formula [24], Wang formula [25], Denisov-Khudenko (DK) formula [26], AKRE formula [27], Ren et al formulas [28], New Ren et al formulas [29], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Refs. [16,17], the Coulomb potential was used in a theoretical investigation of the half-life of certain nuclei. The real potential V(r) is obtained by using the double folding potential given as:…”
Section: The Optical Model Potentialmentioning
confidence: 99%